Pharma spill an engaging student podcast series - Rohaizat, Nurul Asyiqin; Azhar, Nur Iwanie Irdina; Mahamood, Maziana; Karuppannan, Mahmathi (Faculty of Pharmacy, 2026)
The PharmaSpill is an innovative podcast initiative developed to engage students, faculty members, and the wider community through dynamic and interactive interview sessions.Each episode was thoughtfully curated to address key phases of a pharmacy student’s journey, encompassing academic excellence, professional readiness, and long-term career development. By leveraging digital media platforms, PharmaSpill aims to strengthen networking opportunities and foster a sense of community within the pharmacy profession by connecting academicians, alumni, industry practitioners, and the general public.